STRATEGI PENGEMBANGAN PASAR TRADISIONAL BERBASIS KEARIFAN LOKAL UNTUK MENGENTASKAN KEMISKINAN DI BALI - Sukaatmadja, I Putu Gde; Kerti Yasa, Ni Nyoman; Rahyuda, Henny; Widagda, I G. A. Ngr Jaya (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 8 Nomor 2 Tahun 2014, 2013)
The aim of this research is to formulate development strategy of traditional market based on local wisdom to alleviate poverty. This study was taken in Bali Province. The sample determined by nonproportionate random sampling. The samples were 18 heads of traditional market in Bali. The data processed by SWOT analysis with Internal External Matrix (IE Matrix). The result shows that the opportunities consists of income percapita, inflation growth, traditional market revitalisation policy, stabilisation, social awareness, community appreciation, communiy taste changes, and adoption of information technology, the threats were the existence of modern market and population growth. The future strengths are product diversify, local product differentiation, product quality, merchandise layout, price flexibility, and strategy location. Whereas, the weaknesses are parking area availabilitry, transaction process, promotion, cooperation with tourism industry, market cleanliness, public facilitity availability, and consumer services. Based on the SWOT analysis, business position of traditional market are in cell-1 which is further become the basis for development strategy, i.e. “Growth and Maintenance Strategy”
Keywords: opportunity, strengt, weakness, business position, development strategy